Database modeling with Microsoft Visio for Enterprise Architects - Halpin, T. A. (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2003)
This book is for database designers and database administrators using Visio, which is the database component of Microsoft's Visual Studio .NET for Enterprise Architects suite, also included in MSDN subscriptions. This is the only guide to this product that tells DBAs how to get their job done. Although primarily focused on tool features, the book also provides an introduction to data modeling, and includes practical advice on managing database projects. The principal author was the program manager of VEA's database modeling solutions. Explains how to model databases with Microsoft® Visio for Enterprise Architects (VEA), focusing on tool features. Provides a platform-independent introduction to data modeling using both Object Role Modeling (ORM) and Entity Relationship Modeling (ERM), and includes practical advice on managing database projects. Additional ORM models, course notes, and add-ins available online.
Includes bibliographical references and index.
Keywords: Microsoft Visio; Database design; Database management; Electronic books